Comparative Analysis of "Day of the Week" Impact on Bank Nifty Before and After The Introduction of Weekly Option Expiry - Parulekar, Pushkar Dilip (SFIMAR Research Review, 2020)
Historically, Bank Nifty has exhibited more volatility than Nifty and so to facilitate hedging of tradersâ€™ positions weekly option expiry was first introduced on Bank Nifty from May 27, 2016. Since then, Bank Nifty option contracts are settled on every Thursday of the week based on the closing of the Bank Nifty index in the cash market segment. This study will consider two time frames viz. from May 2012 to April 2016 (i.e., before) and from May 2016 to April 2020 (i.e., after) the introduction of weekly option expiry. Five days of the week (Monday, Tuesday, Wednesday, Thursday and Friday) would be considered for both these time frames to check the â€œDay of the Weekâ€ impact on Bank Nifty. Based on daily observations of returns and volatility in returns for both before and after periods it would be checked if there is significant change in the daily Bank Nifty returns. Two Sample t-Test (5% significance) would be used for the same. To test the â€œDay of the Weekâ€ impact for both before and after period, ANOVA with (5% significance) would be used.